Assistance Of Understanding Financial Technology (Fintech) In Easy Financial Access to Msme PWM DKI Jakarta - Ummu Salma Al Azizah; Eti Rohaeti (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
This seminar and training is intended to provide an understanding of the benefits of financial technology in helping people to access finance globally. By providing an understanding of the benefits and functions of existing financial technology, individuals or business actors can manage well and completely planned. It will be easy to plan cash flow that occurs in business units and for future purposes. With the seminar approach given directly to the community, it is expected that there will be discussions and direct questions and questions about the impact of financial technology in human life in general, and financial goals in particular. As a result of the provision of seminars and also training on financial technology, people feel more ability to access financial technology and can implement their financial planning by using financial technology.